Eksplorasi Persepsi Pengguna Terhadap Ketersediaan Layanan Pelanggan E-Wallet - Fatah, Khoirul; Rizaldi, Herna (Neraca, 2024)
This research aims to explore and understand in depth users' perceptions of the availability of customer service in the context of using digital wallets (e-wallets). The main focus is to analyze how users interpret and evaluate the availability of e-wallet customer service, as well as the extent to which these factors influence the overall usage experience. The methods used include data collection through surveys, where respondents will be asked to share their experiences regarding the availability of customer service from the e-wallets they use. Data analysis will be carried out to identify patterns, trends and critical aspects that influence user perceptions about the availability of e-wallet customer service. It is hoped that the results of this research will provide deeper insight into how the availability of customer service can influence e-wallet use, as well as provide a basis for service providers to improve the user experience by better understanding user needs and expectations in terms of customer service. REFERENSI Alam, M. M., Awawdeh, A. E., & Muhamad, A. I. Bin. (2021). Using e-wallet for business process development: challenges and prospects in Malaysia. Business Process Management Journal, 27(4), 1142–1162. https://doi.org/10.1108/BPMJ-11-2020-0528 Biduri, S., Hariyanto, W., Loekitasari, S., & Irma Suryani, A. (2021). Apakah Pendekatan Technology Acceptance Model (TAM) Berpengaruh Terhadap Intention To Use E-Money? In Jurnal Akuntansi Integratif (Vol. 7, Issue 1). Daragmeh, A., Sági, J., & Zéman, Z. (2021). Continuous intention to use e-wallet in the context of the covid-19 pandemic: Integrating the health belief model (hbm) and technology continuous theory (tct). Journal of Open Innovation: Technology, Market, and Complexity, 7(2). https://doi.org/10.3390/joitmc7020132 Esawe, A. T. (2022). Understanding mobile e-wallet consumers’ intentions and user behavior. Spanish Journal of Marketing - ESIC, 26(3), 363–384. https://doi.org/10.1108/SJME-05-2022-0105 Ghozali, I. (2018). Aplikasi Analisis Multivariate Dengan Program IBM SPSS 25 Edisi 9 (9th ed.). Undip. Intarot, P. (2018). Influencing Factor in E-Wallet Acceptant and Use. International Journal of Business and Administrative Studies, 4(4), 167–175. https://doi.org/10.20469/ijbas.4.10004-4 Jogiyanto, H. (2016). Metodologi Penelitian Bisnis Salah Kaprah dan Pengalaman-Pengalaman. Edisi 6. In Yogyakarta: BPFE. BPFE. Karim, M. W. et all. (2020). Factors Influencing the Use of E-wallet as a Payment Method among Malaysian Young Adults. Journal of International Business and Management, 3(2), 1–11. https://doi.org/10.37227/jibm-2020-2-21/ Prakosa, A., & Jati Wintaka, D. (2020). Analisis Faktor-Faktor Yang Mempengaruhi Minat Penggunaan Ulang E-Wallet Pada Generasi Milenial Di Daerah Istimewa Yogyakarta (Vol. 3, Issue 1). Sakdiyah, L., Effendi, R., Kustono, A. S., & Kalimantan, J. (2019). Analisis Penerimaan Penggunaan E-Learning dengan Pendekatan Theory of Planned Behavior ( TPB ) pada Mahasiswa Akuntansi Universitas Jember ( Analysis The Acceptance and The Use of E-Learning with Theory of Planned Behavior ( TPB ) Approach on Jember Unive. VI(1), 120–126. Upadhayaya, A. (2012). Electronic Commerce and E-wallet. International Journal of Recent Research and Review, I(March), 37–41. Wulandari, I. R., & Sumadi, S. (2020). Analysis of Behavior Using E-money With A TAM Approach (Technology Acceptance Model). Manajemen Bisnis, 10(1), 24. https://doi.org/10.22219/jmb.v10i1.10861